A review on plant fiber reinforced thermoset polymers for structural and frictional composites. (November 2020) - Chaudhary, Vijay; Ahmad, Furkan
Abstract: In recent past years, utilization of synthetic materials has become a matter of immense concern due to increasing environmental awareness in terms of safety, sustainability and maintaining ecological balance. A substantial amount of work has been carried out on various aspects of plant based natural fiber reinforced thermoset polymer composite materials due to their numerous inherent properties like high specific strength, low cost and degradability. Current issues and challenges associated with mechanical and tribological properties of only plant based natural fiber reinforced thermoset composites have been highlighted in the present study. Various factors influencing mechanical and tribological characteristics have been discussed keeping the focus on plant fiber reinforced thermoset composites. A detailed discussion on mechanical (tensile, compressive, flexural, impact strength) and tribological properties (friction and specific wear rate) have been reported. Interfacial adhesion was found to be a dominating factor with respect to mechanical and tribological properties. Wear and frictional characteristics of plant fiber based thermoset composites can be controlled using suitable fillers and reinforcement orientation. A discussion on interfacial adhesion and its effect on composite performance have also been included. Highlights: Natural fiber reinforced thermoset polymer composites offers comparable mechanical properties along with high degree of sustainability. Current issues and challenges associated with processing and characterization of only plant based natural fiber reinforced thermoset composites have been highlighted in the study. A detailed discussion on mechanical (tensile, compressive, flexural, impact strength) and tribological properties (friction and specific wear rate) have been reported. A discussion on interfacial adhesion and its effect on composite performance have also been included.